Understanding women's help-seeking for problematic and unhealthy alcohol use through the lens of complexity theory. Issue 2 (12th April 2022) - Cane, Tam Chipawe; Newton, Paul; Foster, John
Abstract : Purpose: It is well established that women face multiple barriers accessing treatment for problematic and unhealthy alcohol use, but less is known about how their interconnected problems affect how they seek help from, and access, alcohol-treatment services. This study aims to explore the dynamic nature of women's help-seeking for problematic and unhealthy alcohol use and how this can be compounded by unsuitable treatment services, especially when women present with complex needs. Design/methodology/approach: Thirteen semi-structured interviews with women who had accessed alcohol-support services were conducted, audio-recorded, transcribed and analysed thematically using the complexity theory. Findings: For women with complex needs, the process of seeking help may trigger unpredictable behaviours, health or social problems and intermittent serial access to treatment. Current services do not always address women's holistic needs. Unless services focus on addressing interconnected problems – including historic trauma – they may compound the complexity of women's problems. Complexity theory offers novel insights into this process, a concept not applied to problematic and unhealthy alcohol use treatment previously. Research limitations/implications: Services should adopt the complexity-focused perspective featured in this study. While the authors acknowledge the increase in gender-responsive provision, the limitations of this study include a small sample size, the self-selecting nature of the sample and retrospective reporting. Participants were recruited and selected by service staff resulting in gatekeeping and possible sampling bias. Practical implications: Services should adopt non-linear approaches to treatment. Implementing complexity approaches to treating women's problematic and unhealthy alcohol use should capture the dynamics, complexity and non-linear nature of women's help-seeking journeys as well as their internal and external responses that may result in relapse. The authors recommend complexity-focused, multiple-component and integrated collaborative strategies to address not only addiction but also all components of women's needs, including past trauma. Originality/value: Applying complexity-thinking to help-seeking experiences for alcohol treatment and recovery services is novel and proved useful in understanding the variety of women's experiences and how these interact with their help-seeking behaviours, including treatment environments.